Measuring Students’ Mathematical Literacy in Culturally Responsive Mathematics Classroom - Ega Gradini; Firmansyah Firmansyah (AT-TA'LIM, 2019)
This paper aims to discuss students’ mathematics literacy in culturally responsive mathematics classroom. Students were taught by culturally responsive mathematics material and examined with a series of test in order to measure their mathematics literacy level. The data collected in this study are quantitative data in the form of scores on students' mathematical abilities that indicate the level of student mathematics literacy. The research was conducted at MAN 1 Takengon with the two groups pre-test and post-test design to determine the differences in mathematical literacy skills of one experimental group and then compare the results with one control group that was not subjected to treatment. The test consists of 6 problems and designed by based on the domain of PISA 2015 questions on every level of mathematical proficiency skills. The research finds that (1) culturally responsive mathematic teaching gives positive effect to students’ mathematical literacy; (2) the level of mathematical literacy of MAN 1 Takengon students lies from level 1 to level 5. There was no student who able to achieve 6thlevel of mathematical literacy; and (3) After culturally responsive mathematics teaching was implemented, from 24 students, there were 4 students at 1st level, 7 students at 2nd level, 10 students at 3rd level, and 2 students at 4th level, and 1 student at 5th level of mathematical literacy.